Pronunciation Errors in Reading Arabic Text of Students of SMPIT Ihsanul Fikri Mungkid - Adam Ghozali Reynaldo Suharto; Muhammad Jafar Shodiq (IKIP PGRI Bojonegoro, 2024)
The objective of the present investigation was to examine the pronunciation errors made by students while reading Arabic text. The study aimed to identify the common pronunciation errors and investigate the underlying causes of these mistakes. The research methodology involved administering reading tests and audio recordings to 20 seventh-grade students (10 male and 10 female) from SMPIT Ihsanul Fikri Mungkid. The collected data was then subjected to qualitative analysis. The study's findings revealed that the students made a variety of pronunciation errors while reading Arabic text, including mispronunciations of vocals, consonants, double consonants, and diphthongs. The analysis also identified a few typical causes of these pronunciation errors. The implications of these findings underscore the importance of addressing pronunciation issues in the context of learning Arabic. The research findings can guide teachers in developing targeted interventions to improve students' Arabic pronunciation, thereby enhancing their overall proficiency through frequent practice and specialized interventions.